Antifungal activity of novel synthetic peptides by accumulation of reactive oxygen species (ROS) and disruption of cell wall against Candida albicans - Maurya, Indresh Kumar; Pathak, Sarika; Sharma, Monika; Sanwal, Hina; Chaudhary, Preeti; Tupe, Santosh; Deshpande, Mukund V.; Chauhan, Virander Singh; Prasad, Rajendra (Peptides, 2011)
In the present work, we investigated the antifungal activity of two de novo designed, antimicrobial peptides VS2 and VS3, incorporating unnatural amino acid alpha,beta-dehydrophenylalanine (Delta Phe). We observed that the low-hemolytic peptides could irreversibly inhibit the growth of various Candida species and multidrug resistance strains at MIC(80) values ranging from 15.62 mu M to 250 mu M. Synergy experiments showed that MIC(80) of the peptides was drastically reduced in combination with an antifungal drug fluconazole. The dye PI uptake assay was used to demonstrate peptide induced cell membrane permeabilization. Intracellular localization of the FITC-labeled peptides in Candida albicans was studied by confocal microscopy and FACS. Killing kinetics, PI uptake assay, and the intracellular presence of FITC-peptides suggested that growth inhibition is not solely a consequence of increased membrane permeabilization. We showed that entry of the peptide in Candida cells resulted in accumulation of reactive oxygen species (ROS) leading to cell necrosis. Morphological alteration in Candida cells caused by the peptides was visualized by electron microscopy. We propose that de novo designed VS2 and VS3 peptides have multiple detrimental effects on target fungi, which ultimately result in cell wall disruption and killing. Therefore, these peptides represent a good template for further design and development as antifungal agents. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Antifungal peptides; Candida albicans; Cell wall; ROS